PROPAEDEUTICS OF ERRORS IN ABSTRACTS OF PAPERS WRITTEN IN RUSSIAN - Oksana L. Dobrynina (Высшее образование в России)
The author considers the ways to prevent errors and mistakes in English language abstracts of papers written in Russian by university faculty, post+graduate students and students earning their Master’s degree in engineering. Common errors have been identified and systematized. The articleprovides examples of common lexical and grammar errors and errors of style and their presumable roots. The process of training includes ‘writing for training’ and ‘writing for communication’ stages. During the second one the studentsread and analyze some samples of abstracts, write their own drafts and discuss them inclass (peer+to+peer review). As a result the quality of abstracts has improved and the number of errors and mistakes has decreased significantly.